Endocarditis Prophylaxis in Cardiac Patients: Knowledge among General Dental Practitioners in Tabriz - Ardeshir Lafzi; Nader Abolfazli; Amir Eskandari (Tabriz University of Medical Sciences, 2008)
Background and aims. Dental procedures injuring oral tissues may induce bacterial release to blood stream that can cause infective endocarditis in susceptible patients. The aim of this study was to determine the level of knowledge of general dental practitioners (GDPs) in Tabriz, Northwest of Iran, regarding endocarditis prophylaxis in cardiac patients receiving dental treatments. Materials and methods. This was a cross-sectional, descriptive, analytical study that included 150 GDPs. All practitioners were given a self-administered questionnaire which consisted of three parts assessing their knowledge of cardiac diseases requiring prophylaxis, dental procedures requiring prophylaxis, and antibiotic regimen for endocarditis prophylaxis. Statistical analysis of data was carried out using independent t-test, one-way ANOVA and chi-square test. Results. The level of knowledge among GDPs in three areas of cardiac diseases requiring prophylaxis, dental procedures requiring prophylaxis, and antibiotic regimen for endocarditis prophylaxis were 63.7%, 66.8% and 47.7%, respectively. Their overall level of knowledge regarding endocarditis prophylaxis was 59%. Association of the level of knowledge with age and practice period was statistically significant (P < 0.05). However, the level of knowledge was not significantly associated with gender or university of graduation in either of three areas evaluated (P > 0.05). Conclusion. According to our results, the knowledge of endocarditis prophylaxis among GDPs in Tabriz was in a moderate level. Regarding the importance of endocarditis prophylaxis in susceptible patients, it should be more emphasized in the curriculum of dental schools and continuing dental education programs.